2012
DOI: 10.1371/journal.pone.0030920
|View full text |Cite
|
Sign up to set email alerts
|

Introspective Minds: Using ALE Meta-Analyses to Study Commonalities in the Neural Correlates of Emotional Processing, Social & Unconstrained Cognition

Abstract: Previous research suggests overlap between brain regions that show task-induced deactivations and those activated during the performance of social-cognitive tasks. Here, we present results of quantitative meta-analyses of neuroimaging studies, which confirm a statistical convergence in the neural correlates of social and resting state cognition. Based on the idea that both social and unconstrained cognition might be characterized by introspective processes, which are also thought to be highly relevant for emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
201
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 224 publications
(221 citation statements)
references
References 91 publications
17
201
2
1
Order By: Relevance
“…Consistent with published meta-analyses (Schilbach et al, 2012;Spreng et al, 2009), this revealed common functional responses in the dmPFC and ventromedial PFC, the TPJ bilaterally, the anterior STS, and the precuneus/posterior cingulate cortex ( Table 2). The medial and transverse slices in Figure 1B show widespread, distributed correspondence between these two ostensibly unrelated contrasts.…”
Section: Within-subject Neuroimaging Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with published meta-analyses (Schilbach et al, 2012;Spreng et al, 2009), this revealed common functional responses in the dmPFC and ventromedial PFC, the TPJ bilaterally, the anterior STS, and the precuneus/posterior cingulate cortex ( Table 2). The medial and transverse slices in Figure 1B show widespread, distributed correspondence between these two ostensibly unrelated contrasts.…”
Section: Within-subject Neuroimaging Resultssupporting
confidence: 88%
“…Here, we consider a function of the DMN that is suggested by a second fact about the human brain: The anatomical boundaries of the DMN largely correspond with the neuroanatomy associated with adopting the intentional stance (Mars et al, 2012;Schilbach et al, 2012;Spreng, Mar, & Kim, 2009;Schilbach, Eickhoff, Rotarska-Jagiela, Fink, & Vogeley, 2008). Importantly, this anatomical coincidence does not permit the conclusion that spontaneous DMN at rest is functionally relevant for adopting the intentional stance in response to social stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it might have an impact on default mode function, given the relevance of socio-affective processes within this network (Schilbach et al 2012). Thus, high-impulsive individuals might have a lesser tendency to remain in the default mode state than low impulsive.…”
Section: Different Neural Parameters and Impulsivity Account For The mentioning
confidence: 99%
“…Rather than actually experiencing the own mental states in first-person perspective, the second-person perspective makes possible to reflect and introspect about the own mental states. That is for instance the case when we ask ourselves whether it is really true that I heard the voice from another person speaking out there in the environment (see also Schilbach et al 2013).…”
Section: Neuronal Findings Iiib: Social Relationship Between Self Andmentioning
confidence: 99%
“…Various studies have been conducted to investigate different kinds of interaction between different selves. Pfeifer et al (2013) and Schilbach et al (2013) distinguish two different methodological approaches. One can investigate social cognition, the cognition of other people's mind, from the outside and thus from an observer's point of view.…”
Section: Neuronal Findings Iiib: Social Relationship Between Self Andmentioning
confidence: 99%